A novel application for oil palm empty fruit bunch: extraction and modification of cellulose for solid polymer electrolyte - Abouloula, Cheyma Naceur; Rizwan, Muhammad; Selvanathan, Vidhya; Abdullah, C.I.; Hassan, Aziz; Yahya, Rosiyah; Oueriagli, Amane (Springer Verlag (Germany), 2018)
Biopolymer-based materials from renewable sources are the core target of the researchers in modern time. Following this motivation, we have developed solid polymer electrolytes (SPEs) from empty fruit branch (EFB) of oil palm. The cellulose was extracted from EFB and modified to carboxymethyl cellulose (CMC) by its reaction with monochloroacetic acid in a strongly alkaline medium. The samples were characterized by FTIR, 13 C NMR, and XRD to confirm the presence of different functional groups, new connectivity, and crystalline/amorphous nature of the materials, respectively. The CMC-based SPEs were fabricated by blending it with different quantities of lithium iodide (LiI) as dopant. The existence of polymer-salt interactions was revealed by FTIR analysis. The maximum ionic conductivity of 5.58 × 10 −3 S cm −1 was observed on sample containing 65 wt% LiI with the lowest activation energy of 0.249 eV.